Effectiveness of brief mindfulness intervention in reducing psychological distress among family caregivers of cancer patients - Anak Agung Sri Sanjiwani; Ketut Lisnawati (Universitas Ahmad Dahlan, 2025)
Family caregivers are particularly vulnerable to psychological distress due to the cumulative burden of caregiving responsibilities and the challenges of balancing their own personal needs. Mindfulness-based approaches have been widely recognized as promising strategies for alleviating psychological distress. This study aimed to examine the effectiveness of a Brief Mindfulness Intervention (BMI) in reducing psychological distress among family caregivers of breast cancer patients. A quasi-experimental design was employed, and purposive sampling was used to recruit 30 family caregivers (15 in the intervention group and 15 in the control group). The intervention consisted of a single 90-minute session, and psychological distress was assessed using the DASS-21. The findings indicated significant reductions in depressive symptoms, anxiety, and stress following the BMI (depression: p = 0.002; anxiety: p = 0.000; stress: p = 0.000). Cohen’s d effect size demonstrated that BMI produced substantial effects, particularly on anxiety and stress (depression: d = 0.43338; anxiety: d = 1.6170; stress: d = 1.1240). These results suggest that BMI may serve as a feasible and preliminary coping strategy for mitigating psychological distress among family caregivers facing emotionally demanding caregiving situations.